in-silico analysis suggests alterations in the function of XisA protein as a possible mechanism of butachlor toxicity in the nitrogen fixing cyanobacterium Anabaena sp. PCC 7120 - Singh, Shilpi (Biomedical Informatics, 2013)
Butachlor, a commonly used herbicide adversely affects the nitrogen fixing capability of Anabaena, an acclaimed nitrogen fixer in the Indian paddy fields. The nitrogen fixation in Anabaena is triggered by the excision of nifD element by xisA gene leading to rearrangement of nifD forming nifHDK operon in the heterocyst of Anabaena sp. PCC7120. Functional elucidation adjudged through in-silico analysis revealed that xisA belongs to integrase family of tyrosine recombinase. The predicted functional partners with XisA protein that have shown cooccurence with this protein in a network are mainly hypothetical proteins with unknown functions except psaK1 whose exact function in photosystem I is not yet known. The focus of this study was to find out the relation between XisA and butachlor using in-silico approaches. The XisA protein was modeled and its active sites were identified. Docking studies revealed that butachlor binds at the active site of XisA protein hampering its excision ability vis-à-vis nif genes in Anabaena sp. PCC7120. This study reveals that butachlor is not directly involved in hampering the nitrogen fixing ability of Anabaena sp. PCC7120 but by arresting the excision ability of XisA protein necessary for the functioning of nif gene and nitrogen fixation.